S101 Src/bcr-abl Inhibition With Dasatinib In Sterile And Non-sterile Acute Lung Inflammation. (10th November 2014) - Macfarlane, JG; Dorward, DA; Lucas, CD; Scott, JA; Ruchaud-Sparagano, MH; Khan, CMA; Rossi, AG; Simpson, AJ
Abstract : Introduction and objectives: Adult respiratory distress syndrome (ARDS) is a commonly fatal complication of lung infection and inflammation, with no effective treatment. It is characterised by excessive neutrophil influx and degranulation into the lungs, with alveolar leak and severe hypoxia. Src family tyrosine kinases are critical in integrin-dependent neutrophil degranulation. Dasatinib is a Src/Bcr-abl inhibitor used in chronic myeloid leukaemia. We investigated our hypothesis that extracellular neutrophil degranulation could be inhibited by dasatinib in vitro and would modulate the inflammatory response in vivo in models of infective and sterile lung injury. Methods: Whole blood and isolated blood neutrophils from healthy volunteers were pre-treated with dasatinib and treated with neutrophil stimuli or live bacteria. Degranulation was measured by granule receptor expression and presence of extracellular granule products. Other neutrophil functions were assessed, including adhesion, L-selectin shedding, chemotaxis, phagocytosis, oxidative burst, bacterial killing and apoptosis. Neutrophilic lung inflammation was induced in mice using intratracheal E. coli or hydrochloric acid. Results: In vitro, dasatinib inhibited neutrophil degranulation in response to lipopolysaccharide derived from E. Coli 026:B6, fMLF and Staphylococcus aureus at concentrations above 100 nM, with no effect on neutrophil viability or apoptosis. Integrin-dependent functions including adhesion, chemotaxis and phagocytosis in adherent conditions were impaired, but phagocytosis was unaffected in whole blood. Intracellular oxidative burst was maintained, with normal bacterial killing, but extracellular superoxide anion release was impaired. In vivo, dasatinib had modest effects on the pro-inflammatory response to E. coli, reducing%interstitial neutrophils, alveolar myeloperoxidase and TNFα at 1 mg/kg and alveolar lactoferrin at 10 mg/kg. Bacterial killing was impaired in a dose dependent fashion, with associated alveolar leak and systemic toxicity at 10 mg/kg. In sterile acid injury, 5 mg/kg dasatinib reduced%neutrophils, degranulation (interstitial CD11b/alveolar lactoferrin) and monocyte-chemotactic protein-1 (MCP-1) in the alveolar space, but induced detrimental effects at 10 mg/kg. Conclusions: The pan- Src kinase inhibitor dasatinib modifies multiple pro-inflammatory neutrophil functions in vitro and in vivo with an impairment in bacterial killing observed in infective lung injury. In the context of sterile inflammation, manipulation of neutrophil degranulation also alters the inflammatory environment and this approach warrants further study as a therapeutic strategy in ARDS.